Apnea induction for invasive lung function testing in infant olive baboons: Comparison of intravenous propofol versus hyperventilation. Issue 1 (12th October 2017) - Ivanov, Vadim A.; Wolf, Roman F.; Papin, James F.; Anderson, Michael P.; Hill, Claude L.; Welliver, Robert C.
Abstract: Background: In various types of pulmonary research, pulmonary function testing (PFT) is performed to quantify the severity of lung disease. Induction of apnea and positive pressure ventilation are required for accurate PFT measurements in non‐cooperative subjects. We compared two methods of apnea induction in infant olive baboons ( Papio anubis ). Methods: Pulmonary function testing results were compared during apnea induced by hyperventilation (CO2 washout) vs. intravenous propofol (1 dose 10 mg/kg). PFT was evaluated using a hot‐wire pneumotachometer incorporated within an Avea ventilator in nine 1‐month‐old baboons. Results: Propofol induced apnea faster and more reliably. In both groups, PFT values passed the statistical equivalence test and were not significantly different (Student's t ‐test). There was a trend toward less data variability after propofol administration. Conclusions: Intravenous propofol was non‐inferior to CO2 washout for apnea induction in infant olive baboons. Propofol induced apnea faster and more reliably and yielded less variable PFT results.